Factors influencing the research participation of adults with autism spectrum disorders - Haas, Kaaren; Costley, Debra; Falkmer, Marita; Richdale, Amanda; Sofronoff, Kate; Falkmer, Torbjorn (Springer, 2016)
The recruitment and retention of adults with autism spectrum disorders (ASD) into research poses particular difficulties; longitudinal studies face additional challenges. To date, factors influencing the participation of adults for ASD research have been unexamined. This article draws on a study conducted in 2014 to identify factors influencing the participation of adults in longitudinal autism research. Quantitative and qualitative data was obtained from 167 participants across Australia in four categories: adults with either high-functioning autism or Asperger syndrome; adults with ASD and an intellectual disability; carers of these adults; and neuro-typical adults. This article includes results for adults with ASD and their carers. Factors influencing participation were found to differ both between and within participant categories. These factors were classified as those arising from a participant’s values, which acted as either a motivator or a deterrent; and those based on convenience, which acted as either an enabler or inhibitor. While helping others was a key motivator for all, participants also sought personal benefits, which differed between categories. Belonging to a research community of like-minded people was also a motivator and enabler. The inconvenience of time and travel required was a key inhibitor; insensitivity to an individual’s needs and preferences for engaging with the world a key deterrent; maximising choice in all aspects of participant involvement a vital enabler; and the use of financial and other extrinsic rewards was found to be problematic.